2020
DOI: 10.1111/ecc.13328
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of competitive cognitive models in explanation of women breast cancer screening behaviours using structural equation modelling: Health belief model and theory of reasoned action

Abstract: Introduction The efficacy of the theory of reasoned action (TRA), compared with the health belief model (HBM), has not been fully elucidated in screening practices. Methods This population‐based cross‐sectional study was conducted with samples of 500 women aged 35–85 years, in the north of Iran. The data of demographic characteristics, awareness, health belief, subjective norms and screening behaviours were collected using standard instruments. Structural equation modelling (SEM) was applied to estimate the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…On a personal level, possessing knowledge increases intentions to adopt healthy behaviors [24]. Specifically, in the case of breast cancer, it acts as a mediating factor in predicting breast cancer screening practice [5,25]. Additionally, as the HBM suggests, an absence of knowledge directly affects perception [2].…”
Section: Discussionmentioning
confidence: 99%
“…On a personal level, possessing knowledge increases intentions to adopt healthy behaviors [24]. Specifically, in the case of breast cancer, it acts as a mediating factor in predicting breast cancer screening practice [5,25]. Additionally, as the HBM suggests, an absence of knowledge directly affects perception [2].…”
Section: Discussionmentioning
confidence: 99%
“…On a personal level, possessing knowledge increases intentions to adopt healthy behaviours [24]. Speci cally, in the case of breast cancer, it acts as a mediating factor in predicting breast cancer screening practice [5,25]. Additionally, as the HBM suggests, an absence of knowledge directly affects perception [2].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Polat et al ( 2021 ) expanded trust and social norms in airline services, directly and indirectly, affecting air travel intentions by reducing perceived risks. Firouzbakht et al ( 2021 ) found moderating health beliefs and subjective norms (indirect beta = 0.35) exert a greater indirect effect on behavioral intentions and a higher intention coefficient (β = 0.626) was observed for subjective norms. This study draws from previous studies to formulate hypotheses 4 and 5 to examine the acceptance of tourists by residents of Hainan impacted by the COVID-19 pandemic.…”
Section: Theoretical Model Construction and Research Hypothesesmentioning
confidence: 99%